Determination of pregnancy in the first quarter by the ultrasonic Doppler - Castro Nestarez, Dante (2015)
This work was done with the intention to make a firm diagnosis of pregnancy in the first trimester, since at this stage, often Therapeutic positions should be dependent on fetal vitality. The study involved 250 pregnant women whose gestational age ranged between 6 and 14 weeks, and varied own pathology of this quarter. An ultrasound equipment that uses the Doppler Effect (brand SONIC-AID) was used. The advantages of this method over others, primarily safety, easy implementation and immediate results, place it as a weapon of choice in the daily practice of Obstetrics.